Problematika Pendaftaran Tanah Bagi Ahli Waris Keturunan Tionghoa Yang Perkawinan Orang Tuanya Tidak Tercatat - Rismawaty Rismawaty; Dedi Harianto; T. Keizerina Devi Azwar; Faisal Akbar (Iuris Studia: Jurnal Kajian Hukum, 2021)
Registration of property rights is part of land registration. Article 19 paragraph (1) of the LoGA stipulates that "To guarantee legal certainty by the government, land registration is held throughout the territory of the Republic of Indonesia according to the provisions stipulated by Government Regulation." The implementation of land registration activities is an obligation of the government which aims to guarantee legal certainty that is rechtscadaster, meaning that it is for the benefit of land registration only and is only concerned with what rights and who owns it, not for other interests such as taxation. The formulation of the problem in this study is 1) How is the determination of heirs to the transfer of land rights of Chinese descent based on Inheritance according to the Provisions for Land Registration in Indonesia?, 2) What are the obstacles to registering the transfer of land rights obtained by heirs of Chinese descent based on inheritance if the marriage of their parents not registered at the civil registry office? 3) What are the efforts to solve the problem to overcome the problem of registering the transfer of land rights obtained by heirs of Chinese descent based on inheritance if the marriage of their parents is not registered at the civil registry office? The type used in this research is normative juridical. Sources of data used in this study is secondary data consisting of primary legal materials, secondary legal materials and tertiary legal materials